Improving Adolescents' Reproductive Health Knowledge Through Animated Video Education on Vulva Hygiene - Lintang Ayu Diana Linsqy; Diana Tri Lestari; Ashri Maulida Rahmawati (Program Studi S1 Keperawatan Universitas Ngudi Waluyo, 2025)
A common problem among adolescent girls is a lack of understanding about proper vulva hygiene, which increases the risk of reproductive tract infections. This study aimed to determine the effect of education using animated videos about vulva hygiene on adolescents' knowledge of reproductive health. This study used a quantitative approach with a quasi-experimental pre- and post-test design with a control group. The population and sample consisted of 50 Grade XI IPS students at MA Darul Ulum Purwogondo, selected using total sampling and divided into 25 students in the intervention group and 25 students in the control group. The instrument used was a valid and reliable knowledge questionnaire, while the educational media was an interactive animated video. Data analysis was performed using the paired sample t-test and independent t-test. The results showed a significant increase in the intervention group, with an average knowledge score of 5.20 before education and an increase to 6.92 after education (p < 0.001). Meanwhile, the control group experienced a decrease in scores from 4.80 to 4.64 (p = 0.54). A comparison between the two groups showed a statistically significant difference (p = 0.00). Thus, education using animated videos proved to be effective in increasing adolescents' knowledge about reproductive health. These results imply that visual educational media can be used by school nurses to provide interesting and informative health education for adolescent girls.